2022
DOI: 10.1038/s41467-022-33367-w
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-7 regulates melanocortin circuits involved in mammalian energy homeostasis

Abstract: MicroRNAs (miRNAs) modulate physiological responses by repressing the expression of gene networks. We found that global deletion of microRNA-7 (miR-7), the most enriched miRNA in the hypothalamus, causes obesity in mice. Targeted deletion of miR-7 in Single-minded homolog 1 (Sim1) neurons, a critical component of the hypothalamic melanocortin pathway, causes hyperphagia, obesity and increased linear growth, mirroring Sim1 and Melanocortin-4 receptor (MC4R) haplo-insufficiency in mice and humans. We identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 120 publications
1
29
0
Order By: Relevance
“…Previous studies have identified the involvement of miR-7 in response to oxidative stress 37 , in particular to low glucose 38 . To establish the possible functional link between the upregulation of miR-7 in ciRS-7 KO mice in conditions of ischemic stroke, we subjected cre-loxP inducible miR-7 KO mice 39 to tMCAo (Figure 5A, Supplementary Figure S4A,B). We failed to detect changes in the lesion volume as measured by MRI between miR-7 KO and WT mice at acute timepoint (1dpi) (Supplementary Figure S4C).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have identified the involvement of miR-7 in response to oxidative stress 37 , in particular to low glucose 38 . To establish the possible functional link between the upregulation of miR-7 in ciRS-7 KO mice in conditions of ischemic stroke, we subjected cre-loxP inducible miR-7 KO mice 39 to tMCAo (Figure 5A, Supplementary Figure S4A,B). We failed to detect changes in the lesion volume as measured by MRI between miR-7 KO and WT mice at acute timepoint (1dpi) (Supplementary Figure S4C).…”
Section: Resultsmentioning
confidence: 99%
“…Of note is that murine neuroblastoma cell lines express negligible amounts of ciRS-7 even when differentiated with retinoic acid, suggesting a more direct effect of miR-7 in the absence of its regulator. A recent study has highlighted a potential role of miR-7 in controlling energy homeostasis in hypothalamic neurons 39 , linking this miRNA to conditions in which the energetic balance is strongly altered, such as in ischemic stroke. However, alteration in the levels of miR-7 in hypothalamic neurons were not accompanied by changes in the expression of ciRS-7 or Cyrano 39 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations